Development of purple rice beverage product by corn malt enzymes - Manonun, Nunnapat; Boonkum, Satain; Chaiyaso, Thanongsak; Seesuriyachan, Phisit (Food and Applied Bioscience Journal, 2017)
The objective of this study was to develop a beverage from purple rice by using corn malt enzymes.The optimum condition for the production of enzymes was the ratio of corn malt per water of 1:4 and thecondition of extraction was 60°Cfor 180 min. The highest amylase activity was 503.12±2.29 U/g malt. The process of saccharification by using 20% of malt extract and 20% of streamed purplerice incubated at 90°C for 360 min gave the highest soluble solid andreducing sugar content with 11.00±0.20°Brix and 737.78±10.78 mg/ml, respectively. Sensory evaluation scores of the 4 samples of the purple rice beverage product with the mixture of streamed purple rice was 5%, 0%, 15% and 20% (w/w) by using 9-Piont hedonic scale scoring test with 50panelists, the highest overall preference of the purple rice beverage product was the mixture with 20% (w/w) of streamed purple rice.